CoronARe: A coronary artery reconstruction challenge - Cimen, Serkan; Unberath, Mathias; Frangi, Alejandro; Maier, Andreas (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2017)
CoronARe ranks state-of-the-art methods in symbolic and tomographic coronary artery reconstruction from interventional C-arm rotational angiography. Specifically, we benchmark the performance of the methods using accurately pre-processed data, and study the effects of imperfect pre-processing conditions (segmentation and background subtraction errors). In this first iteration of the challenge, evaluation is performed in a controlled environment using digital phantom images, where accurate 3D ground truth is known.
CRIS-Team Scopus Importer:2022-06-05
Keywords: 3D reconstruction; Angiography; C-arm Cone-beam CT; Motion compensation